(untitled) (Hekima Review, 2014)
The Lord’s Prayer is universally appealing because of its contents. This means that outside the liturgical use of the Christian community, interreligious gatherings could pray the Our Father without any crisis of faith. This research work explores thetheological significance of the 6th and 7th petitions of the Our Father: “And lead us not into temptation but deliver us from all evil.” The true meaning of these petitions is effectively discussed by referring to the Greek meanings of the following key words: “lead”, “temptation”, “deliver”, and “evil”. This enabled us to affirm that in the sixth petition we ask God to preserveus from sinning whenever we are tempted. This affirmation recognizes the necessity and the indispensability of temptation in the formational experiences of a Christian. The “evil” which we pray to be delivered, in the seventh petition, has both temporal and eschatological dimensions. Its eschatology is understood from the perspective of the history of salvation. This research thus leads to the conclusion that articulates the Our Father as a compendium of the Gospel of Christ since it shapes our Christian identity.